2008
DOI: 10.1111/j.1399-302x.2008.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the presence of T helper type 17 cells in chronic lesions of human periodontal disease

Abstract: These results provided strong evidence for the presence of Th17 cells in the sites of chronic inflammation in human periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
206
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(237 citation statements)
references
References 35 publications
(47 reference statements)
21
206
1
9
Order By: Relevance
“…Numerous reports have shown an elevated level of IL-17 in gingival tissues or gingival crevicular fluid from periodontitis lesions compared with healthy sites [50][51][52][53][54][55][56][57]. These reports also demonstrated the association of other Th17-related cytokines (eg, IL-1β, IL-6, IL-21, and IL-23) with periodontitis.…”
Section: Cd4supporting
confidence: 55%
“…Numerous reports have shown an elevated level of IL-17 in gingival tissues or gingival crevicular fluid from periodontitis lesions compared with healthy sites [50][51][52][53][54][55][56][57]. These reports also demonstrated the association of other Th17-related cytokines (eg, IL-1β, IL-6, IL-21, and IL-23) with periodontitis.…”
Section: Cd4supporting
confidence: 55%
“…This suggests that IL-21 may be derived from other cell types such as Th17 cells. Recent studies demonstrated the presence of Th17 cytokine in periodontitis tissues (9,54). However, the ability of this T cell subset in producing IL-21 in periodontitis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have revealed dense inflammatory cell infiltration, involving T cells, B cells and macrophages in periodontitis affected regions [1][2][3]. Recently, a new type of T cell, Th17, has been linked with several inflammatory diseases [4], and it was reported that Th17 cells are present in periodontally diseased tissues [5]. However, the effect of IL-17A, which is produced from Th17, on Th17 migration in periodontally diseased tissues is uncertain.…”
Section: Introductionmentioning
confidence: 99%